Soil warming affects sap flow responses to meteorological conditions for Betula albosinensis at a subalpine wetland in the edge of northeast Qinghai–Tibet Plateau. Issue 3 (22nd February 2019) - Yan, Chunhua; Takeuchi, Shinichi; Qiu, Guo Yu
Abstract: Transpiration in cold‐limited areas is restricted by low soil temperature. However, little is known about the influence of soil warming on tree transpiration under a water logged and cold soil conditions. We aimed to test the hypothesis that an increase in soil temperature in the absence of water stress will lead to increased sap flow of red birch ( Betula albosinensis ) in a subalpine wetland. Sap flow and relevant environmental data were measured for B. albosinensis in a subalpine wetland in the edge of northeast Qinghai–Tibet Plateau from 2013 to 2016. The cooling and controlling experiments were also conducted in the lab from June to July in 2017. The results showed that meteorological parameters, as well as soil temperature, are important limiting factors for tree transpiration. It was governed by meteorological factors throughout the growing season, whereas we only found a significant increase of sap flow upon soil warming in the mid‐growing season, which may be attributed to warm‐induced hydraulic conductivity. In the early growing season, no warming effect was observed on sap flow. We then concluded that whole‐tree water use may increase with increasing soil temperature and similar precipitation and thus alter the local water balance. These results are essential to understand the response of hydrological processes to future climate warming.